Konsep Manusia Sempurna dalam Perspektif Kautsar Azhari Noer - Dimas Dwi Putra; Mohd. Arifullah; Nurdin Nurdin (STIKes Ibnu Sina Ajibarang, 2025)
This article explores the concept of insan kamil (the perfect human) from the perspective of Kautsar Azhari Noer, a prominent contemporary Muslim thinker. Noer integrates the classical Sufi philosophical framework with the challenges of modern human civilization. According to Noer, the perfect human is not only defined by spiritual proximity to God but also by the ability to reflect divine values in intellectual, ethical, and cultural dimensions. Using a qualitative, literature-based approach, this study analyses Noer's interpretations in relation to classical sources such as Ibn ʿArabī and Al-Jīlī. The findings show that Noer offers a philosophical reinterpretation of insan kamil as a response to modern existential and moral crises.